Writing the discussion - Ng, K.H.; Peh, W.C. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
The discussion section comprises the last component in the IMRAD system. The purpose of this section is to provide the interpretation of the results obtained, explain the implications of the findings, state study limitations and make suggestions for future research. This is a critical part of the scientific paper, as it places the particular study within the broader context of how the research contributes to improving diagnosis, treatment or patient care.